Survival analysis of platinum‐refractory patients with advanced esophageal cancer treated with docetaxel or best supportive care alone: a retrospective study. Issue 8 (11th June 2014) - Moriwaki, T.; Kajiwara, T.; Matsumoto, T.; Suzuki, H.; Hiroshima, Y.; Matsuda, K.; Hirai, S.; Yamamoto, Y.; Yamada, T.; Sugaya, A.; Kobayashi, M.; Endo, S.; et al.
Summary The survival benefit of second‐line chemotherapy with docetaxel in platinum‐refractory patients with advanced esophageal cancer (AEC) remains unclear. A retrospective analysis of AEC patients with Eastern Cooperative Oncology Group performance status (PS) ≤ 2 was performed, and major organ functions were preserved, who determined to receive docetaxel or best supportive care (BSC) alone after failure of platinum‐based chemotherapy. The post‐progression survival (PPS), defined as survival time after disease progression following platinum‐based chemotherapy, was analyzed by multivariate Cox regression analysis using factors identified as significant in univariate analysis of various 20 characteristics (age, sex, PS, primary tumor location, etc) including Glasgow prognostic score (GPS), which is a well‐known prognostic factor in many malignant tumors. Sixty‐six and 45 patients were determined to receive docetaxel and BSC between January 2007 and December 2011, respectively. The median PPS was 5.4 months (95% confidence interval [CI] 4.8–6.0) in the docetaxel group and 3.3 months (95% CI 2.5–4.0) in the BSC group (hazard ratio [HR] 0.56, 95% CI 0.38–0.84, P = 0.005). Univariate analysis revealed six significant factors: treatment, PS, GPS, number of metastatic organs, liver metastasis, and bone metastasis. Multivariate analysis including these significant factors revealed three independent prognostic factors: docetaxel treatment (HR 0.62, 95% CI 0.39–0.99, P = 0.043), better GPS (HR 0.61, 95% CI 0.46–0.81, P = 0.001), and no bone metastasis (HR 0.31, 95% CI 0.15–0.68, P = 0.003). There was a trend for PPS in favor of the docetaxel group compared with patients who refused docetaxel treatment in the BSC group (adjusted HR 0.61, 95% CI 0.29–1.29, P = 0.20). Docetaxel treatment may have prolonged survival in platinum‐refractory patients with AEC.